The role of communication in hospital health promotion - Wardani, Riana (Padjadjaran Journal of Dentistry, 2007)
The health promotion program is an effort to help society in improving healthy attitudes. It also can teach people to help themselves how to deal with health problems. Hospital workers have an important role to distribute health information in terms of improving the lives of individuals (themselves, patients) and the health of environment.It is inevitably that hospital workers are heterogenic due to their education (paramedic: doctor, nurse; non paramedic: administration, cleaning service), and their tasks and responsibility (superior, subordinate). However, in their hospital service duties, they should be collaborative each others. Moreover, they should be strengthening their commitment to serve any patient or client by ignoring their economic condition, education, or disease complaining as well.In conclusion, good communication between hospital workers and patient, between hospital worker themselves, hospital worker and society as well is a significant sign that health promotion program is success.